Level Ketaatan Konsumsi Kombucha Bunga Telang Sebagai Minuman Probiotik Bagi Pasien Kolesterol Yang Berasal Dari Kampung Pekuncen Cilegon Banten - Husein, Ahmad Saddam Saddam; Rezaldi, Firman; Trisnawati, Desi; Fadillah, M. Fariz; Pamungkas, Barolym Tri; Ginaris, Rifkarosita Putri; Somantri, Ucu Wandi; Sasmita, Heny (Jurnal Ilmiah Farmasi Attamru (JIFA), 2026)
An increase in the amount of Low Density Lipoprotein (LDL), triglycerides, and High Density Lipoprotein (HDL) which tends to decrease is known as high cholesterol or hypercholesteromia. Cholesterol treatment is generally carried out through chemical therapy which has pharmacological activity as a cholesterol lowerer, namely simfastatin. The side effects of chemical treatment are stomach inflammation, liver and kidney damage, and increased resistance. The solution offered to minimize chemical cholesterol treatment is by using butterfly pea flower kombucha as a probiotic drink which has been proven to be used as a functional food substance, medicine and cosmetic, so that adherence to consuming flower kombucha is an indicator of success in lowering cholesterol levels. This study aims to determine the level of patient compliance in consuming butterfly pea flower kombucha in an effort to lower cholesterol. This research method was carried out descriptively and the sampling technique was carried out by purposive sampling. The results of this study have proven that patient compliance at a high level reached 24.40%, medium 68.30%, low 7.33% so it can be concluded that high cholesterol patients who were carried out in Pekuncen village, Ciwedus village, Cilegon city, Banten province had a moderate level of compliance with percentage of 68.30%.